Conference on Lasers and Electro-Optics 2022
DOI: 10.1364/cleo_si.2022.sw4k.6
|View full text |Cite
|
Sign up to set email alerts
|

Hollow-core fibers with ultralow loss in the ultraviolet range and sub-thermodynamic equilibrium surface-roughness

Abstract: We report on hollow-core fibers displaying rms core roughness under the surface capillary waves thermodynamic limit and record loss in the short-wavelength range (50.0dB/km at 290nm, 9.7dB/km at 369nm, 5.0dB/km at 480nm, 0.9dB/km at 558nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…To extend the study of nonlinearity and power efficiency in the green power delivery using HCF technology, we modeled a lowerloss HC-ARF and simulated the spectral bandwidth broadening and output powers based on the similar fiber geometry used in this work but with the fiber loss scaled to 1.8 dB km −1 at 520 nm (minimum loss of 1.5 dB km −1 at 560 nm, based on the state-ofthe-art loss level achievable [11,14] ) and the similar sub-nanosecond pulses but with higher input peak power (up to 150 kW). To study spectral broadening, the spectral bandwidth Δ𝜆 is defined and calculated by integrating spectral power around both sides of the input wavelength (520 nm) after broadening that contains at least 80% of the total power.…”
Section: Nonlinear Investigation and Scalability Of Power Delivery In...mentioning
confidence: 99%
See 2 more Smart Citations
“…To extend the study of nonlinearity and power efficiency in the green power delivery using HCF technology, we modeled a lowerloss HC-ARF and simulated the spectral bandwidth broadening and output powers based on the similar fiber geometry used in this work but with the fiber loss scaled to 1.8 dB km −1 at 520 nm (minimum loss of 1.5 dB km −1 at 560 nm, based on the state-ofthe-art loss level achievable [11,14] ) and the similar sub-nanosecond pulses but with higher input peak power (up to 150 kW). To study spectral broadening, the spectral bandwidth Δ𝜆 is defined and calculated by integrating spectral power around both sides of the input wavelength (520 nm) after broadening that contains at least 80% of the total power.…”
Section: Nonlinear Investigation and Scalability Of Power Delivery In...mentioning
confidence: 99%
“…Hundreds of millions of kilometers of standard solid single-mode fiber (SMF) are installed each year to transmit relatively low power extending from the ultraviolet, through the visible and nearinfrared, and out even to the mid-infrared. [10][11][12][13][14][15] Power delivery systems on the scale of hundreds of meters have been successfully implemented in the near and mid-infrared laser wavelength region. [1,13,16] However, no long-range power delivery in the visible region has yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Yu et al reported a ARF with attenuation of 0.08 dB/m and 0.26 dB/m at 218 nm and 355 nm, respectively in 2017 [ 25 ]. In most recent work on UV HCFs, Osório et al reported a method to reduce the inner surface roughness of HCFs by improving the preparation process [ 26 ]. Their method can achieve a reduction in the root-mean-square of surface roughness from 0.40 nm to 0.15 nm, reducing the loss figure as low as 9.7 dB/km at 369 nm [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implication is that more complex designs which primarily further reduce the leakage loss at similar core sizes are not necessary for fibers operating in this region. Thus in principle, the simpler tubular designs can be optimized to provide the lowest loss possible in this spectral region (see for example [104]. Similarly, at wavelengths beyond about 2.5µm, the loss is dominated by IR absorption.…”
mentioning
confidence: 99%